RUTE TERPENDEK ALGORITMA PARTICLE SWARM OPTIMIZATION DAN BRUTE FORCE UNTUK OPTIMASI TRAVELLING SALESMAN PROBLEM - Muchamad Kurniawan; Farida Farida; Siti Agustini (JURNAL TEKNIK INFORMATIKA, 2021)
Distribution becomes an important measure of marketing success. Traveling Salesman Problem is an example of a case that can be implemented in a distribution case study to get the shortest route through which a distributor passes. The distributor must pass each node (address or city) once in a while and then return to the node where he started. Traveling salesman problems emerge as part of logistical and transportation problems that have developed and utilized in the current period which is growing in various sectors. This research proposes using the Particle Swarm Optimization and Brute Force method to compare the performance of the two methods to get the shortest route. The study was conducted in several experiments the number of points (nodes) namely 5, 10, 15, 20, 25, and 30 nodes. Overall experiments, the Particle Swarm Optimization algorithm is superior to Brute Force. The route produced by Particle Swarm Optimization has a shorter distance than Brute Force